A experiência amorosa de Deus no comentário ao Cântico dos Cânticos de Orígenes - Ribeiro, Francisco Erlânio Gomes (2019)
In the Commentary of Canticle of the Canticles, by Origen, the loving experience of God appears figuratively in the characters of both of the beloveds. Text belonging to the set of wisdom books, the Canticle of Canticles was interpreted, by determined judaic tradition, as prototype between God and His people Israel. This spousal image, which expresses the covenant of love between God and His people, is present in the book of Hosea, representing the prophetic literature. In the New Testament, we find no ipsis litteris references to the wisdom text, but allusions that place the lector in a nuptial context. Some parables of Jesus are found also in the context of marriage (cf. Mt 22,1-13; 25,1-13). Saint Paul presents the Church as the bride (cf. 2Cor 11,2) and Christ as the Bridegroom (cf. Eph 5: 22-23). In patristic literature, Origen of Alexandria (A.D 185-254) was the first great commentator of Canticle of the Canticles. Unlike previous interpretations, Origen interprets the wisdom text as allegory of love between the Word of God and the soul (psychological reading). Throughout his Commentary on the Canticle of the Canticles, the relationship of the lovers is marked by the intermittence, presence and absence of the Bridegroom. With the moving theme of love throughout the book, our actor considers it opportune to clarify that it is said in agape and eros ways. He also notes that, for prudence, the term eros hardly appears in the biblical text. For Origen, this divorce between agape and eros is not appropriate, since in both ways of loving have, in God, its origin and destiny. Moreover, in the spiritual itinerary the soul must to be inflamed by the desire to move her towards the Bridegroom. She appears wounded by the husband's loving dart. In the wife who loves, the human capacity to love is figured. The itinerary is always two-way: sometimes the wife is described in anguishing wait, sometimes presented in a frenetic nocturnal search for the beloved; sometimes it is the beloved who watches through the crack of the door the beauty of the beloved. To this movement of love, especially on the part of the beloved, our author called divine philanthropy. For love, the Word of God has come to dwell within humanity. The events of Christ's life are situated in the perspective of divine love. The wife is invited to contemplate the humanity of Jesus to ascend to the contemplation of his divinity. This is possible only by the awakening of the spiritual senses. In the origenian spiritual journey, the loving experience of God is situated in a crescent that embraces the creature from pre-existence to the moment when “God be all in all” (1Cor 15:28)